Proceedings of the 50th Hawaii International Conference on System Sciences (2017) 2017
DOI: 10.24251/hicss.2017.438
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fitbits in Corporate Wellness Programs: Does Step Count Matter?

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 36 publications
0
37
0
2
Order By: Relevance
“…Therefore, real-time awareness might trigger an implicit durable behavior change [9]. Giddens et al [13] conducted a study with 53 participants, and found that using an activity tracker has a positive impact on steps taken, which has a positive impact on wellbeing and health. They also found, however, that users reported increased wellbeing regardless of their step count and attributed this to the fact "that the device itself may raise awareness of one's physical activity and the importance of a healthy lifestyle that includes physical movement" [13:3632].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, real-time awareness might trigger an implicit durable behavior change [9]. Giddens et al [13] conducted a study with 53 participants, and found that using an activity tracker has a positive impact on steps taken, which has a positive impact on wellbeing and health. They also found, however, that users reported increased wellbeing regardless of their step count and attributed this to the fact "that the device itself may raise awareness of one's physical activity and the importance of a healthy lifestyle that includes physical movement" [13:3632].…”
Section: Introductionmentioning
confidence: 99%
“…As Cederström and Spicer (2015) underline, selftracking should not be seen as a benign attempt to locate and try to fix flaws or weaknesses; instead, it is about reconstructing oneself according to specific market requirements. As the measured body has the potential to become more productive and generate more profits, data-driven corporate wellness programs are attracting increasing interest among employers, as they can lead to significant reductions in healthcare costs because of perceived positive impacts on employees' health and well-being (Giddens et al 2017). However, the health benefits of using these devices are being questioned.…”
Section: Datafication and Platformization Of Healthcarementioning
confidence: 99%
“…Successful comprehensive wellness programs included health education, a supportive social and physical environment, organizational integration, links between the wellness program and similar programs, and health screenings followed by education and counseling (Goetzel et al, 2012;Mitchell et al, 2013). Some included physical activity components using Fitbits (Giddens, Leidner, & Gonzalez, 2017). Fitbits, wearable pedometers, were found to be effective tools for improving physical activity in employee wellness programs, including the optional features that were found to improve step count (Giddens et al, 2017).…”
Section: Review Of Relevant Literature To Guide Our Programmentioning
confidence: 99%